Correction: Relationship between Smoking and Obesity: A Cross-Sectional Study of 499,504 Middle-Aged Adults in the UK General Population. - Shadrach Dare; Daniel F Mackay; Jill P Pell (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0123579.].